MICROPERIMETRY AND MORPHOMETRIC PARAMETERS OF OPTIC NERVE HEAD AND MACULAR AREA IN PATIENTS WITH PRIMARY OPEN ANGLE GLAUCOMA - B. M. Aznabaev; A. Sh. Zagidullina; A. A. Alexandrov (Oftalʹmologiâ, 2017)
Purpose: To study by using microperimetry a degree of functional disorders of retinal peripapillary area in patients with initial stage of primary open angle glaucoma (POAG), to analyze correlation relationship of the microperimetry parameters and the main morphometric parameters of the optic nerve head (OND).Patients and methods. There were 51 patients (98 eyes) in the study aged from 50 to 72 years (average age 58,37 ± 9,41 years) with the initial stage of POAG. The control group consisted of 50 somatically healthy persons (99 eyes) without ophthalmological pathology. In addition to the standard ophthalmologic examination, the special methods included: optical coherence tomography (OCT) of the posterior segment of the eye (Optovue Avanti RTVue XR, USA) and microperimetry (Macular Integrity Assessment (MAIA), USA). Statistical analysis of the received data were processed with the IBM SPSS Statistics v.21 program (standard methods of descriptive statistics).Results. Microperimetry has shown a significant statistical difference of MI parameters (29,68 ± 23,18) and AvTh (27,63 ± 3,38 dB) in patients with initial stage of POAG from those in the control group (p <0,01). The highest correlation of morphometric parameters and microperimetry parameters was defined in MI patients with POAG with the focal loss of volume (FLV) of ganglion cells complex (GCC) (ρ = 0,642, p <0,001). A significant positive relationship of moderate strength was found between microperimetry parameter MI in patients with POAG and the FVL GCC (ρ = 0,346, p <0,01), a moderate negative relationship with the index of MI was obtained with an average GCC thickness (ρ = -0,378, p <0 , 01), and an average RNFL thickness (ρ = -0,355, p <0,01). In patients with POAG a significant moderate positive relationship of AvThr parameter was identified with BCVA (ρ = 0,324, p <0,01), a moderate negative relationship of AvThr parameter with age (ρ = -0,401, p <0,01).Conclusion. Application of microperimetry confirms involvement of the macular area in the pathological process in POAG. In the early stages of glaucoma neuroretinopathy is manifested both as regarding microperimetry functional data and OCT morphometric parameters.